Prevalence and prognostic value of c-kit and TP53 mutations in canine mast cell tumours - Vozdova, Miluse; Kubickova, Svatava; Fictum, Petr; Fröhlich, Jan; Jelinek, Frantisek; Rubes, Jiri (The veterinary journal, 2019)
Cutaneous mast cell tumours (MCT) are among the most frequent malignancies in dogs. Their clinical behaviour is highly variable and, with the exception of mutations in the c-kit gene, little is known about their genetic aetiology. The mutational status of the c-kit exons 8, 9 and 11, and exons 5-8 of the TP53 gene was analysed to find markers for molecular stratification of MCTs and predictors of clinical outcome. Mutations in the c-kit gene were detected in 19.5% (n = 8/41) samples and their presence was significantly associated with the high histopathological grade (P = 0.038). Mutations in the DNA binding domain of the TP53 gene were found in 14.6% (n = 6/41) of the analysed MCTs, and their frequency was similar in low and high grade MCTs (P > 0.05). TP53 mutations were not useful prognostic factors in this sample of canine cutaneous MCTs.
Keywords: psi; kožní mastocytóza; nádory kůže; Dogs; Skin Neoplasms; Proto-Oncogene Proteins c-kit; protoonkogenní proteiny c-kit; nádorový supresorový protein p53; mutace; frekvence genu; zvířata; Neoplasm Grading; nemoci psů; prognóza; stupeň nádoru; Gene Frequency; Mastocytosis, Cutaneous; Dog Diseases; Animals; Mutation; Prognosis; Tumor Suppressor Protein p53